Protein partitioning in poly(ethylene glycol)/sodium polyacrylate aqueous two-phase systems - Johansson, Hans-Olof; Magaldi, Flavio Musa; Feitosa, Eloi [UNESP]; Pessoa, Adalberto (Elsevier B.V., 2008)
The partition of hemoglobin, lysozyme and glucose-6-phospate dehydrogenase (G6PDH) in a novel inexpensive aqueous two-phase system (ATPS) composed by poly(ethylene glycol) (PEG) and sodium polyacrylate (NaPA) has been studied. The effect of NaCl and Na2SO4, pH and PEG molecular size on the partitioning has been studied. At high pH (above 9), hemoglobin partitions strongly to the PEG-phase. Although some precipitation of hemoglobin occurs, high recovery values are obtained particularly for lysozyme and G6PDH. The partitioning forces are dominated by the hydrophobic and electrochemical (salt) effects, since the positively charged lysozyme and negatively charged G6PDH partitions to the non-charged PEG and the strongly negatively charged polyacrylate enriched phase, respectively. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Hemoglobin; lysozyme; Glucose-6-phosphate dehydrogenase; Polyethylene glycol; sodium poly(acrylic acid); Aqueous two-phase systems; Liquid-liquid extraction